Ciudad murada : a walk through historic Intramuros - Torres, Jose Victor Z. (Manila : Intramuros Administration and Vibal Pub. House, 2005)
"Ciudad Murada is a highly interesting and entertaining guide to landmarks--both extant and vanished--and to the history of Manila's Intramuros. It also serves as possible inspiration and guide to policy makers and planners and to private sector developers, as an object lesson on what can be done to recover some of the old glory of Manila The Beautiful." - Dr. Jaime C. Laya
Peering at the past -- Paseo : strolling through Intramuros -- Monuments that survived the centuries -- The moat -- Roads of history
English
Keywords: Historic buildings -- Philippines -- Intramuros, Manila -- Pictorial works; Intramuros, Manila -- History; Intramuros, Manila -- Description -- Guidebooks